The Memorial Art and Architecture of Vicksburg National Military Park - Panhorst, Michael W. (Book collections on Project MUSE., 2014)
"An illustrated guide to Vicksburg's monuments and memorials. Includes an illustrated driving tour that visitors can use as they drive through the park"--Provided by publisher.